2010
DOI: 10.1016/j.annemergmed.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in the Emergency Department: An Independent Predictor of Death Within 6 Months

Abstract: Objectives Delirium’s adverse effect on long-term mortality in older hospitalized patients is well documented, while its effect in older emergency department (ED) patients remains unclear. Similarly, the consequences of delirium on nursing home patients seen in the ED are also unknown. As a result, we sought to determine if delirium in the ED was independently associated with 6-month mortality in older patients and if this relationship was modified by nursing home status. Methods Our prospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
157
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(171 citation statements)
references
References 46 publications
9
157
0
5
Order By: Relevance
“…This corroborates the findings of Han et al,32 which demonstrated a high occurrence of delirium among older adults admitted to an emergency department.…”
supporting
confidence: 82%
“…This corroborates the findings of Han et al,32 which demonstrated a high occurrence of delirium among older adults admitted to an emergency department.…”
supporting
confidence: 82%
“…Incidence of postoperative delirium is high even in a population without known risk factors (Andrea Saporito, 2014). Among all admitted patients, those at highest risk of delirium (87%) are the elderly (aged over 65) (Han et al, 2010;Svenningsen & Tonnesen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the prevalence of delirium ranges from 9.6 to 12.3%, according to different studies. [16][17][18][19] Delirium is associated with a number of adverse clinical outcomes, including increased risk of institutionalization and higher mortality. 12,20,21 In hospital settings, delirium is associated with a nearly double risk of death at 2 years follow-up, independent of important confounders, such as age, sex, comorbidity and dementia.…”
Section: Epidemiology and Outcomes Of Deliriummentioning
confidence: 99%